PERBANDINGAN TINGKAT KEBUGARAN JASMANI SISWA BERINTELIGENSI NATURALIS DENGAN KINESTETIK (STUDI PADA SISWA KELAS VIII SMP YIMI GRESIK) - SYUKRUL AMIN, MOH. (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Physical Education, Sport and Health to the point of physical fitness. SMP Yayasan Islam Malik Ibrohim (YIMI) Gresik is one of schools that use MI. The most important point in MI approach is everyone has eight intelligences or more. They are linguistic, kinesthetic, naturalist, mathematic-logic, musical, interpersonal, intrapersonal and spatial. The objective of this study is to know the comparison of physical fitness level between naturalist and kinesthetic intelligent students, especially at 8 grade student of SMP YIMI Gresik, this research use Multistage Fitness Test (MFT) as a physical fitness test. In this research, applying for purposive sampling  and by use of statiscal data t-test analysis, and sample amounted to fifty one students. Based on statistical data analysis is known that thitung obtained 1,339 < score ttabel 2,011 so it is concluded that Ha is rejected because thitung is smaller than ttabel. In the other words, there is not difference in of physical fitness level between naturalist and kinesthetic intelligent students. Keywords: Physical Fitness, Multiple Intelligences, Naturalist and  Kinesthetic Intelligences.